Utilization of a Swine (Sus scrofa) Model for Lipid Emulsion Resuscitation Studies. (4th December 2012) - Crane, Carrie; Sagini, Eileen; Johnson, Arthur D.; O'Sullivan, Joseph
Abstract : Background . There have been some discussions that using swine or rabbits in a resuscitation model to study lipid emulsion infusions may be inappropriate because of a consistent "pseudoallergic" reaction that has been found in lipid-based nanoparticle liposome drug carrier systems. Assertions have been made that the lipid emulsions may contain a certain amount of liposomes; therefore swine may not be an appropriate model for study. Methods . This study was prospective, crossover design within subjects, and research design with each Yorkshire swine receiving a 20% lipid bolus infusion followed by a lipid infusion for 10 min. Each swine had a total of four blood draws and each draw had complete blood gas analysis with three different types of inflammatory markers examined. Cardio vascular monitoring was performed every 2 minutes. Results . Using data reported in similar studies, a large effect size of 0.6 was calculated. Using the effect size of 0.6, a power of 0.8 and an alpha of 0.05 it was determined that a sample size of five swine was needed. There were no significant changes in any CV parameter both before and after lipid emulsion. Likewise there were no significant changes in any of the blood tests, nor any inflammatory markers. Conclusions . There were no significant changes in the examined parameters with swine before and after lipid emulsion infusions. It is suggested that due to the close size of swine to humans, similar physiology, and ease of using these animals, they may be utilized for lipid emulsion studies.